The Demand for Money: A General-Equilibrium Inventory-Theoretic Approach - Akerlof, George A. (Review of Economic Studies, 1973)
Journal Article The Demand for Money: A General-Equilibrium Inventory-Theoretic Approach Get access George A. Akerlof George A. Akerlof University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 1, January 1973, Pages 115–130, https://doi.org/10.2307/2296743 Published: 01 January 1973